MROS-TXNIP axis activates NLRP3 inflammasome to mediate renal injury during ischemic AKI. (May 2018) - Wen, Yi; Liu, Yi-Ran; Tang, Tao-Tao; Pan, Ming-Ming; Xu, Sheng-Chun; Ma, Kun-Ling; Lv, Lin-Li; Liu, Hong; Liu, Bi-Cheng
Abstract: Ischemia/reperfusion (I/R) is a critical risk factor for acute kidney injury (AKI). Recent studies provided evidence that tubular epithelial cells (TEC)-associated inflammation aggravates kidney injury and impairs tissue repair after I/R injury. Here we demonstrated that the Nod-like receptor protein 3 (NLRP3) inflammasome is activated by mitochondrial reactive oxygen species (mROS) during I/R injury via direct interactions between the inflammasome and thioredoxin-interacting protein (TXNIP). Firstly, we found that NLRP3 inflammasome activation was induced by I/R injury, peaking at day 3 after reperfusion. Consistent with this observation, NLRP3 deletion significantly attenuated I/R-induced kidney damage and markers of inflammasome activation. Then, we observed mitochondrial dysfunction, characterized by ultrastructural changes and cytochrome C (Cyt c) redistribution. Mitochondria-targeted antioxidant MitoTEMPO prevented mROS overproduction and the decline in mitochondrial membrane potential (MMP) in vitro. MitoTEMPO treatment also inhibited NLRP3 inflammasome activation and co-localization of NLRP3 and TXNIP after simulated ischemia/reperfusion (SI/R) injury. Finally, we transfected HK-2 cells with TXNIP siRNA to explore the role of TXNIP in mROS-induced NLRP3 inflammasome activation. We found that TXNIP siRNA significantly inhibited NLRP3 inflammasome activation. These results demonstrate that NLRP3 inflammasome is activated through the mROS-TXNIP-NLRP3 pathway and provide a potential therapeutic target in ischemic AKI.